(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2018)
Background: Surgical treatment is very crucial for the acute subdural hematoma patients. Objective: The purpose of the present study was to compare outcome of decompressive craniotomy with wide opening of dura and multidural fenestration technique. Methodology: This non-randomized clinical trial was carried out in the Neurosurgery Department of Dhaka Medical College Hospital, Dhaka, Bangladesh from January 2011 to August 2012 for a period of one year and eight months. Patients with acute subdural hematoma who fulfil the inclusion criteria for surgery and got admitted were selected as study population. Acute Subdural hematoma patient of any age, both sex with GCS 5 to 13, thickness of hematoma more than l0 mm, midline shift more than 5 mm, pupil reacting to light and patient presented within 72 hours of injury were included for this study. At admission, a detailed history of the illness was taken from the patient or attendant, thorough general and neurological examinations were carried out and were recorded. Specific treatment of head injury started and surgery done, cases were divided into two groups on the basis of surgical technique. Operative details, regular follow-up and post-operative CT scan findings were recorded. Finally GOS scoring done on the day of discharge of patient from the hospital. Result: A total number of 48 patients were recruited of this study of which 25 were in group A and the rest 23 patients were in group B. In group A, according to GOS Score, good recovery was 48%, moderate disability 16%, severe disability (8%), persistent vegetative state 4% and 24% patients died. In group B, good recovery was 47.83%, moderate disability 13.04%, severe disability 4.35%, persistent vegetative state 13.04% and 21.74% patients died. The mean duration of surgery was l26.32±24.86 minutes in group A and 90.95±l8.64 in group B and this difference was highly significant (P<0.00l). In addition, the mean duration of hospital stay was 23.44(±6.65) days in group A and 16.26(±4.63) days in group B and this difference between two group was statistically significant (P<0.001). Conclusion: In conclusion multiple dural fenestrations is an effective decompressive procedure for removal of acute subdural hematoma Journal of National Institute of Neurosciences Bangladesh, 2018;4(2): 75-81